2021
DOI: 10.1016/j.lanwpc.2021.100193
|View full text |Cite
|
Sign up to set email alerts
|

Whole of population-based cohort study of recovery time from COVID-19 in New South Wales Australia

Abstract: Background: COVID-19 results in persisting symptoms but there is little systematically collected data estimating recovery time following infection. Methods:We followed 94% of all COVID-19 cases diagnosed in the Australian state of New South Wales between January and May 2020 using 3-4 weekly telephone interviews and linkage to hospitalisation and death data to determine if they had recovered from COVID-19 based on symptom resolution. Proportional hazards models with competing risks were used to estimate time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 17 publications
(18 reference statements)
0
30
0
1
Order By: Relevance
“… 14 days [ 17 ] 0.655 (0.579 – 0.727) a [ 10 , 11 ] Post-acute consequences (ONS) Start at 25.91% (23.2 to 29.0%) 2 weeks after initial COVID infection [ 18 ] a See notes below on how we compute for the COVID-19 survivors noted in this calculation. 14 days to 2 years (assumed) 0.219 (0.148-0.308) [ 10 , 11 ] Post-acute consequences (NSW) Start at 33.60% (33.0 to 34.0%) 2 weeks after initial COVID infection [ 19 ] See notes below on how we compute for the COVID-19 survivors noted in this calculation. 14 days to 2 years (assumed) 0.219 (0.148-0.308) [ 10 , 11 ] Post-Intensive Care Syndrome (PICS) 90.6% of ICU survivors [ 20 ] See notes below on how we compute for the COVID-19 survivors noted in this calculation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 days [ 17 ] 0.655 (0.579 – 0.727) a [ 10 , 11 ] Post-acute consequences (ONS) Start at 25.91% (23.2 to 29.0%) 2 weeks after initial COVID infection [ 18 ] a See notes below on how we compute for the COVID-19 survivors noted in this calculation. 14 days to 2 years (assumed) 0.219 (0.148-0.308) [ 10 , 11 ] Post-acute consequences (NSW) Start at 33.60% (33.0 to 34.0%) 2 weeks after initial COVID infection [ 19 ] See notes below on how we compute for the COVID-19 survivors noted in this calculation. 14 days to 2 years (assumed) 0.219 (0.148-0.308) [ 10 , 11 ] Post-Intensive Care Syndrome (PICS) 90.6% of ICU survivors [ 20 ] See notes below on how we compute for the COVID-19 survivors noted in this calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Our model assumed that Long COVID symptoms start directly after the symptomatic phase. Briefly, Long COVID refers to those patients experiencing any of the following symptoms: persistent fever, headache, muscle ache, weakness/tiredness/fatigue, nausea/vomiting, abdominal pain, diarrhoea, sore throat, cough, shortness of breath, loss or change of taste, loss or change of smell runny nose and chest pain post COVID-19 infection to reflect the symptoms observed in the studies of Liu et al [ 19 ] and UK ONS cohort study [ 18 ]. Given the United Kingdom (UK) evidence that some patients still report Long COVID over 12 months after infection [ 18 ], our model assumed that Long COVID could potentially last up to 2 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is clear that the majority of unvaccinated individuals survive primary infection without the need for hospitalization (91) what remains to be fully elucidated are the specific immune correlates of protection against SARS-CoV-2 (92)(93)(94). The pandemic will continue until further studies reveal the veritable correlates of protection against SARS-CoV-2 and/or the whole world is immunized, including those most vulnerable to severe COVID-19 such as those living with HIV-1.…”
Section: Challenges Aheadmentioning
confidence: 99%
“…The April 2021 survey by the Office for National Statistics shows 21% of people with confirmed covid-19 still have symptoms at 5 weeks and 13.7% at 12 weeks 4. A recent population based longitudinal study from Australia reported high rates of recovery among adults with confirmed covid-19 (20%, 80%, 93%, and 96% at 10, 30, 90, and 120 days respectively) 5. This indicates that, however distressing the symptoms, most people meeting NICE criteria for long covid are on a path, albeit often fluctuating, to natural recovery.…”
mentioning
confidence: 99%